Serum glucagon, bile acids, and FGF-19: metabolic behavior patterns after Roux-en-Y gastric bypass and vertical sleeve gastrectomy - Yang, Cui; Brecht, Julia; Weiß, Christel; Reißfelder, Christoph; Otto, Mirko; Buchwald, Jane N.; Vassilev, Georgi (Obesity surgery, 2021)
Metabolic/bariatric surgery is a highly effective treatment for obesity and metabolic diseases. Serum glucagon, bile acids, and FGF-19 are key effectors of various metabolic processes and may play central roles in bariatric surgical outcomes. It is unclear whether these factors behave similarly after Roux-en-Y gastric bypass (RYGB) vs vertical sleeve gastrectomy (VSG).
Published online: 30 August 2021
Gesehen am 02.06.2023